2016
DOI: 10.1111/clr.12983
|View full text |Cite
|
Sign up to set email alerts
|

Monophasic ß‐TCP vs. biphasic HA/ß‐TCP in two‐stage sinus floor augmentation procedures – a prospective randomized clinical trial

Abstract: Both monophasic and biphasic materials show good biocompatibility and osteoconductivity with satisfactory support on implant stability. BBS remains more stable in terms of volume maintenance and radiological graft homogeneity after a healing period of 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 34 publications
3
44
0
2
Order By: Relevance
“…However, the percentages of residual graft particles and soft‐tissue areas were similar to the percentage of new bone formation in this group. Results of a recent histomorphometric study supported our findings, which reported that newly formed bone, residual graft particles, and soft‐tissue areas were approximately 30% in β‐TCP bone biopsies obtained 6 months after sinus augmentation. Lezzi et al reported 30.5% of new bone formation 6 months after sinus augmentation with β‐TCP.…”
Section: Discussionmentioning
confidence: 99%
“…However, the percentages of residual graft particles and soft‐tissue areas were similar to the percentage of new bone formation in this group. Results of a recent histomorphometric study supported our findings, which reported that newly formed bone, residual graft particles, and soft‐tissue areas were approximately 30% in β‐TCP bone biopsies obtained 6 months after sinus augmentation. Lezzi et al reported 30.5% of new bone formation 6 months after sinus augmentation with β‐TCP.…”
Section: Discussionmentioning
confidence: 99%
“…For BBSMs, the tissue reaction is formed by the individual reactions towards each of the material compounds. Therefore, aspects such as biodegradation is based on the activity of phagocytes such as macrophages and BMGCs towards the individual compounds (10,12,17,(20)(21)(22)(23)(24)(25)(26). Hence, BBSMs initially induce an inflammatory tissue reaction similar to that of a pure β-TCP material, resulting in a high number of BMGCs and a high degradation rate, at later stages this is followed by a slower degradation rate correlated with lower BMGC numbers at a later, which can be compared to pure HA (17).…”
mentioning
confidence: 99%
“…It has also been revealed that BBSMs induce tissue reactions that may support the bone regeneration process (17,20,32). Thus, BBSMs have been shown to be favorable materials for bone tissue regeneration in different preclinical and clinical studies (10,12,17,20,21,23,24,(32)(33)(34).…”
mentioning
confidence: 99%
“…Se conoce que los concentrados otorgan los factores de crecimiento al β-TCP. De esta forma la neoformación ósea aumentaría, aunque algunos estudios solo han encontrado entre el 19 y el 30 % de formación ósea [34][35][36][37] ; quizás porque no hay beneficio en el aumento de células, vasos capilares y nueva formación ósea, además de que los resultados encontrados a largo plazo no evidenciaron diferencias significativas con los grupos que utilizaron la mezcla PRF y β-TCP 18,38,39 .…”
Section: Discussionunclassified